Types of Figurative Speech in Biak - Arsai, Alfons Napoleon; Arsai, Almendita Flora Wendelmood (Mandalika Institute, 2025)
Biak tribal language is one of the vernaculars spoken in Papua which is categorized as a member of Austronesian phylum and Geelvink bay sub phylum. The speakers of this language are approximately 40.000 people. These people are on islands of Biak, Numfor, numerous islands east and west of Bird’s head, in Manokwari and in northern Bird’s head including Mapia island. There are six dialects in Biak namely, Var Risen, Var Swandiwe, Var Awer, Var Swandivru, Var Dore and Var Eramber. The method used to collect the data is qualitative method by applying descriptive approach to describe the data from the instruments by interviewing. This paper discusses types of figurative speech in Biak related to indirect meanings. The use of figures of speech in Biak society aims to soften the messages conveyed by a speaker indirectly in meaning by using connotative expressions. Descriptive method was used in describing and analyzing the data. The simple techniques in analyzing the data were as follow: (1) provide Biak transcriptions, (2) do English gloss, (3) do free translation and (4) provide the connotative meanings of each figurative speech. From discussion point of view, there are eleven types of figures of speech found in Biak such as similes, hyperbole, personification, euphemisms, synecdoche, methonymy, litotes, irony, metaphor, sarcasm and parable.